Adherence Over Time: The Course of Adherence to Customized Diabetic Insoles as Objectively Assessed by a Temperature Sensor. (May 2018) - Ehrmann, Dominic; Spengler, Monika; Jahn, Michael; Niebuhr, Dea; Haak, Thomas; Kulzer, Bernhard; Hermanns, Norbert
Background: Temperature sensors are an objective way to assess adherence to diabetic footwear. Good adherence is essential for the prevention of diabetic foot problems. Little is known about the long-term course of adherence in patients at risk for diabetic foot problems. Method: A temperature sensor was incorporated into the specialized footwear of patients with type 2 diabetes after their first plantar ulceration. Kaplan-Meier curve was used to analyze when patients started to become nonadherent (not wearing the footwear for two straight weeks). Gender effects on adherence were also analyzed. Results: 26 patients with a mean observation time of 133.5 days could be analyzed. Mean wearing time of diabetic footwear was 4.2 ± 3.6 h/day (Mdn = 3.4 h/day; interquartile range = 0.5-7.0 h/day) and on 51% of the days patients did not wear their footwear at all. Kaplan-Meier curve revealed that the mean time of adherence was 27.5 weeks. Men achieved a mean time of adherence of 30.5 weeks, while women only achieved 14 weeks. However, due to the small sample size, this difference was not statistically significant. Conclusions: Temperature sensors revealed a low long-term adherence to diabetic footwear. Women seemed to be at a higher risk for earlier nonadherent behavior. Adherence to diabetic footwear should be closely monitored and tailored intervention strategies should be developed.